2013
DOI: 10.1038/mi.2012.86
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA induces molecular and inflammatory signatures that are directly relevant to COPD

Abstract: Polyinosinic:polycytidylic acid (poly I:C) is a synthetic analogue of double-stranded (ds)RNA, a molecular pattern associated with viral infections, that is used to exacerbate inflammation in lung injury models. Despite its frequent use, there are no detailed studies of the responses elicited by a single topical administration of poly I:C to the lungs of mice. Our data provides the first demonstration that the molecular responses in the airways induced by poly I:C correlate to those observed in the lungs of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…One mechanism is that viruses promote exacerbations by triggering host inflammatory responses resulting in cellular infiltration, mucous production, airway hyper-reactivity and remodelling (Wedzicha, 2004). Using poly(I:C) as a prototypical viral PAMP that mimics the inflammatory exacerbations of COPD (Harris et al, 2013), we examined the role of the Scgb1a1 -expressing tracheo-bronchiolar epithelial cell as an innate sentinel cell, and specifically, the role of NFκB-BRD4 pathway in mediating airway inflammation. Our findings that selective depletion of RelA in tracheal and bronchiolar epithelial cells prevented BRD4 activation and poly(I:C) induced expression of inflammatory cytokines and IFNs, indicate that epithelial cells are a major sensor of luminal poly(I:C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One mechanism is that viruses promote exacerbations by triggering host inflammatory responses resulting in cellular infiltration, mucous production, airway hyper-reactivity and remodelling (Wedzicha, 2004). Using poly(I:C) as a prototypical viral PAMP that mimics the inflammatory exacerbations of COPD (Harris et al, 2013), we examined the role of the Scgb1a1 -expressing tracheo-bronchiolar epithelial cell as an innate sentinel cell, and specifically, the role of NFκB-BRD4 pathway in mediating airway inflammation. Our findings that selective depletion of RelA in tracheal and bronchiolar epithelial cells prevented BRD4 activation and poly(I:C) induced expression of inflammatory cytokines and IFNs, indicate that epithelial cells are a major sensor of luminal poly(I:C).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also implicated the role of group 2 innate lymphoid cells in the host response to viruses (Peebles et al, 2001). To provide greater insight into the role of the epithelial cell as a sentinel cell responding to viral PAMPs, we developed a conditional knockout (CKO) mouse selectively deleting RelA in tracheo-bronchiolar cells and challenged them with poly(I:C), a viral pattern that simulates acute RNA virus infections in COPD (Harris et al, 2013; Stowell et al, 2009). We observed that poly(I:C) induces mucosal BRD4 (HAT)-dependent histone acetyltransferase (HAT) activity on Histone H3K122 and BRD4-dependent phosphorylation of Ser2 on the RNA Pol II carboxy terminal domain (CTD).…”
Section: Introductionmentioning
confidence: 99%
“…PolyI:C is known to be recognized by toll-like receptor 3 (TLR3) and is best known as an inducer of interferon (IFN), which plays a significant role in viral recognition and activation of innate immunity (Heitmeier et al, 1998;Tissari et al, 2005;Stowell et al, 2009;Hüsser et al, 2011). Thus, PolyI:C is considered a viral-associated dsRNA to mimic viral infection in the study of the immune response of host cells (Heitmeier et al, 1998;Majde, 2000;Geiss et al, 2001;Harris et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a model that uses a viral mimetic, poly I:C, which resulted in a typical inflammatory response [35], ATP spiking increased levels of IL-1β (Figure 8, right panels). Thus we are confident that bacterial and viral infections cause the release of EVs into the airway, and if there are high levels of ATP present in the airway (like in asthma and COPD), it could trigger the release of IL-1β and IL-18.…”
Section: Resultsmentioning
confidence: 87%